2017
DOI: 10.1016/j.diagmicrobio.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid DNA extraction method for Chlamydia trachomatis detection from urogenital swabs

Abstract: A highly sensitive and specific Chlamydia trachomatis (CT) diagnostic test was developed by combining filtration isolation of nucleic acid (FINA) extraction with quantitative polymerase chain reaction including an internal control to identify test inhibition. A pilot study of 40 clinical specimens yielded 100% sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…One current limitation of using extracted blood products is the need for faster methods for routine extraction and detection (Lievens and Thomma, 2005), particularly in the pre-storage stage of sample preparation. Some studies have reported that Triton X-100 and sodium dodecyl sulfate (SDS) surfactants solubilize cell membrane due to hydrophilic and hydrophobic properties (Butzler et al, 2017;John et al, 2018). Additionally, ammonium chloride buffer has been employed to lysis red blood cells (Chernyshev et al, 2008;Horn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One current limitation of using extracted blood products is the need for faster methods for routine extraction and detection (Lievens and Thomma, 2005), particularly in the pre-storage stage of sample preparation. Some studies have reported that Triton X-100 and sodium dodecyl sulfate (SDS) surfactants solubilize cell membrane due to hydrophilic and hydrophobic properties (Butzler et al, 2017;John et al, 2018). Additionally, ammonium chloride buffer has been employed to lysis red blood cells (Chernyshev et al, 2008;Horn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasma marginale DNA was extracted using commercial QIAamp Blood mini kit (Qiagen Inc., USA) which was used as a reference positive extracted DNA. Blood was treated separately with two pre-lysis buffer protocols using Triton X-100 and ammonium chloride as described by Butzler et al (2017) and the fastest pre-lysis procedure was selected and optimized.…”
Section: Reference Positive Controls and Pre-lysis Blood Treatmentsmentioning
confidence: 99%